Assessment of the efficacy of commercial anthelmintics in horses naturally infected with gastrointestinal nematodes - Martins, Natália Soares; Pinto, Diego Moscarelli; Cunha, Laís Leal da; Lignon, Júlia Somavilla; Santos, Thais Cozza dos; Evaristo, Tainá Ança; Pappen, Felipe Geraldo; Nizoli, Leandro Quintana (Medicina Veterinária, 2021)
The objective of this study was to assess the efficacy of commercial anthelmintics in horses naturally infected with gastrointestinal nematodes from the southern Rio Grande do Sul state, Brazil. The anthelmintic efficacy was assessed by fecal egg count reduction test (FECRT) and coproculture. Fecal samples were collected from 110 animals in seven farms located in the southern region of the state of Rio Grande do Sul, in the south of Brazil. Criteria used to suspect anthelmintic resistance included percentages of efficacy lower than 95% and a lower limit of the confidence interval below 90%. Anthelmintic resistance was detected in five of the seven farms studied. Coproculture results show that, even after horses were treated with anthelmintics, infection by nematodes of the subfamily Cyathostominae was still present in animals from five farms.